In bioethical criteria in demonstrative and experimental practices with animals in the Career of Pedagogy in Chemistry and Biology - Murillo-Cumbal, Marjorie (2024)
Demonstrative and experimental studies with animals over time have been part of the practical teaching of different contents that have contributed to the biological, medical and pharmacological sciences. However, progress in scientific and educational activity has brought with it bioethical difficulties from the academic perspective in the importance of using animals to consolidate theoretical knowledge and from the bioethical-legal perspective in the requirement of good animal management. The objective of the research was to analyze the application of bioethical criteria in demonstrative and experimental practices that use animals in the Pedagogy of Experimental Sciences in Chemistry and Biology. The study had a qualitative-descriptive approach. The interview technique was applied to three laboratory professionals and to an external teacher expert in animal practices.  In addition, laboratory observation was carried out using an observation card with nine indicators and four dimensions in 32 practices with animals. A structured survey of 11 questions was also applied. These instruments were applied to a population of 155 students in their third, fourth and eighth semesters. The survey, interview and observation form were validated by three expert teachers. The results indicated that 68.75% of the practices work with dead individuals, 21.87% with insect vivisection and 9.38% with preserved exotic animals.  In conclusion, most of the practices (78.13%) are in accordance with the framework of the Bioethical Regulations set forth at national and international level and have taken care of animal welfare, avoiding unnecessary sacrifice of animals.